Odorant-binding protein 84a-1 mediates detection of Guire No.82 mango volatiles in Bactrocera dorsalis: from structural analysis to behavioral validation - Peng, Peng; Tang, Yingying; Yang, Shian; Mo, Yingxi; Huang, Guodi; Chen, Yongsen (Frontiers in Insect Science, 2026)
Bactrocera dorsalis is a serious pest of mango, causing heavy losses during fruit ripening. Odorant-binding proteins (OBPs) are pivotal in insect olfaction, facilitating the detection of host plant volatiles. In this study, we focused on OBPs that mediate responses to volatiles from the Guire No.82 mango. Quantitative real-time PCR showed cultivar-dependent expression of six antennal OBP genes. Among these, BdorOBP84a-1 was highly expressed in adults fed on Guire No.82. The 3D structure of BdorOBP84a-1 was predicted with AlphaFold3, showing six α-helices and three disulfide bonds forming a hydrophobic pocket. Molecular docking and 100-ns MD simulations indicated strong and stable binding of sesquiterpenes. Caryophyllene and ledene showed the lowest binding free energies (-31.87 and -30.62 kcal/mol) and stable RMSD/RMSF values. Key residues, including PHE95, ILE109 and PHE133, contributed to binding through hydrophobic and aromatic interactions. Y-tube behavioral assays validated these computational predictions. Caryophyllene attracted males at very low (0.01%) and high (10%) doses, females responded selectively at 0.1% and 1%, ledene attracted males at 0.1% and 10%, These findings suggest that BdorOBP84a-1 mediates recognition of mango sesquiterpenes and that caryophyllene and ledene are promising leads for new attractants in B. dorsalis management.